Rectal endometriosis mimicking primary rectal adenocarcinoma. Issue 12 (18th August 2021) - Hu, Jingjing; Hosseini, Mojgon; Hasteh, Farnaz; Murphy, Paul; Pare, Christopher; Kwong, Wilson T.; Patel, Charmi
Abstract: Endometriosis is a benign entity defined as the presence of endometrium tissue outside of uterine cavity. It is a common disease involving peritoneum, pelvic organs, gastrointestinal tract, and so on. Diagnosis based on cytology specimen can be challenge when we encounter increased cytological atypia in the glandular epithelium, with abundant inflammatory cells and debris in the background. We presented a case of deep rectal endometriosis mimicking rectal adenocarcinoma on cytology specimen and on MRI imaging studies. The combination of endometrial glands, cellular Mullerian stroma, hemorrhage, and hemosiderin‐laden macrophages are the characteristic features on cytologic specimens.